Tracheostomy ventilation in motor neurone disease: a snapshot of UK practice. Issue 1 (2nd January 2022) - Palmer, Jonathan; Messer, Ben; Ramsay, Michelle
Abstract: Introduction: Motor neurone disease (MND) is characterized by rapidly progressive motor neurone degeneration which leads to muscle wasting. Mortality and morbidity are due to respiratory muscle failure which may be offset by ventilation. The aim of this observational study was to quantify the number and characteristics of patients living with MND choosing tracheostomy ventilation (TV) in the UK. Methods : Long-term ventilation services in the UK were invited to undertake a retrospective 5-year audit of MND patients under their care between April 2013 and March 2018 who had TV. Patient characteristics, the time spent on ventilation, hospital length of stay, discharge destination, and survival data were collected. Results : Sixty-eight MND patients were initiated on TV over the 5-year period. Eighty-one percent of patients received TV in an emergency setting with more than a third of these undiagnosed at presentation. Patients choosing elective TV were more likely to be male (85%) have a bulbar presentation (54%) and an increased survival of 10 months over the observation period. The mean length of hospital stay post TV was 136 days. Two-thirds of patients were discharged to their own home. Conclusion : Very few patients living with MND in the UK are currently receiving TV. In those who choose TV, there may be a survival advantage to planning an elective procedure. Despite the long inpatient stay and high care costs involved a majority of patients survived and were discharged to their own home.